'Doing things together': male caregivers' experiences of giving care to patients in forensic psychiatric care. Issue 1 (26th February 2012) - KUMPULA, E.; EKSTRAND, P.
<x xml:space="preserve">Abstract</x> Accessible summary The view that male caregivers have of the provision of care is based on social and cultural ideas of masculinity. Experiences of giving care are based on relationships with each other and on their view of what can lead to recreating health. Activities constitute a natural part of giving care in forensic psychiatric care. The objective of the activities means that patients and personnel share activities. These activities are to contribute to deepening and reinforcing care‐based relationships and creating opportunities for recreating health. Activities can be coupled to the provision of care on a ward and associated with the inner environment, routines and tasks such as cooking, cleaning, washing and shopping. One interpretation is that these activities can be understood as social and cultural acts that distinguish the provision of care by men from tasks that can be experienced with connotations from traditional female‐gendered tasks. Abstract Studies into work carried out by male caregivers in a care environment in which male patients and male caregivers constitute a majority are lacking. The purpose of this study was to illuminate the experiences of male caregivers in providing care for patients in forensic psychiatric care. The study has a qualitative design and data were constituted by interviews with six male caregivers at a clinic of forensic psychiatry in a town in central Sweden. The method of analysis chosen was latent content analysis. The results consist of four themes: Activities as a component of care, Social training as the basis of care, Feelings of powerlessness and Seeing the complete person. The experience that comes out most distinctly in the descriptions given by caregivers involves performing activities together with the patients. The activities had different significances and these contribute to creating a more secure care relationship, in which the boundaries between personnel and patients become less clear. Physical activities contribute to recreating the patient's health. Social training appears as a component of the care in which the significance of rules and routines in the operations was integrated. Feelings of powerlessness arise when the caregivers do not experience that the care given on the ward contributes to recreating health for the patients. Seeing the complete person behind the crime constitutes the themes that can be said to summarize the meaning of the work carried out by male caregivers.